Role of normal sleep and sleep apnea in human memory processing - Ahuja S (Dove Medical Press, 2018)
Shilpi Ahuja,1 Rebecca K Chen,1 Korey Kam,1 Ward D Pettibone,1 Ricardo S Osorio,2 Andrew W Varga1 1Mount Sinai Integrative Sleep Center, Division of Pulmonary, Critical Care, and Sleep Medicine, Icahn School of Medicine at Mount Sinai, New York, NY, USA; 2Center for Brain Health, Department of Psychiatry, NYU School of Medicine, New York, NY, USA Abstract: A fundamental problem in the field of obstructive sleep apnea (OSA) and memory is that it has historically minimized the basic neurobiology of sleep’s role in memory. Memory formation has been classically divided into phases of encoding, processing/consolidation, and retrieval. An abundance of evidence suggests that sleep plays a critical role specifically in the processing/consolidation phase, but may do so differentially for memories that were encoded using particular brain circuits. In this review, we discuss some of the more established evidence for sleep’s function in the processing of declarative, spatial navigational, emotional, and motor/procedural memories and more emerging evidence highlighting sleep’s importance in higher order functions such as probabilistic learning, transitive inference, and category/gist learning. Furthermore, we discuss sleep’s capacity for memory augmentation through targeted/cued memory reactivation. OSA – by virtue of its associated sleep fragmentation, intermittent hypoxia, and potential brain structural effects – is well positioned to specifically impact the processing/consolidation phase, but testing this possibility requires experimental paradigms in which memory encoding and retrieval are separated by a period of sleep with and without the presence of OSA. We argue that such paradigms should focus on the specific types of memory tasks for which sleep has been shown to have a significant effect. We discuss the small number of studies in which this has been done, in which OSA nearly uniformly negatively impacts offline memory processing. When periods of offline processing are minimal or absent and do not contain sleep, as is the case in the broad literature on OSA and memory, the effects of OSA on memory are far less consistent. Keywords: consolidation, learning, REM sleep, sleep spindles, slow oscillations